2016
DOI: 10.1159/000452449
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Fibrosing Alopecia and Vitiligo: Coexistence or True Association

Abstract: Frontal fibrosing alopecia (FFA) is a primary lymphocytic cicatricial alopecia characterized by a progressive band-like recession of the frontotemporal hairline and frequent loss of the eyebrows. It predominantly affects postmenopausal women. Coexistence of FFA and vitiligo is rarely reported in the literature. We retrospectively studied 20 cases diagnosed with FFA in a 14-month period in our Department. Among them, there were 2 cases, a 72-year-old woman and a 48-year-old man, who developed FFA on preexisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 37 publications
3
17
2
7
Order By: Relevance
“…We found a strong association between FFA and LPP, which were associated in almost 1/4 of the patients, suggesting that FFA represents a clinical variant of LPP, with an autoimmune pathogenesis. According to literature, 3,[12][13][14][15][16][17] we found a significant prevalence of other autoimmune diseases (50.8%) in our patients and a high percentage of patients with atopic background (35.4%), suggesting a possible personal predisposition to immune system disorders.…”
Section: Discussionsupporting
confidence: 64%
“…We found a strong association between FFA and LPP, which were associated in almost 1/4 of the patients, suggesting that FFA represents a clinical variant of LPP, with an autoimmune pathogenesis. According to literature, 3,[12][13][14][15][16][17] we found a significant prevalence of other autoimmune diseases (50.8%) in our patients and a high percentage of patients with atopic background (35.4%), suggesting a possible personal predisposition to immune system disorders.…”
Section: Discussionsupporting
confidence: 64%
“…In a retrospective study of 20 cases diagnosed with FFA at our Academic Department during a 14‐month period, there were two patients, a 72‐year‐old female and a 48‐year‐old male, who developed FFA on preexisting vitiligo of the forehead. Anatomical colocalization supports the hypothesis that a causal link may exist, in terms of interrelated immunologic events and pathologic processes that may underlie both these skin conditions . Furthermore, we studied prospectively 27 females (mean age 67 years) with FFA and found that eight (29.6%) had autoimmune thyroiditis with positive anti‐thyroid autoantibodies, and five (18.5%) had subclinical hypothyroidism with negative autoantibodies…”
supporting
confidence: 67%
“…0.2–0.5 %). Individual case reports and small case series have repeatedly suggested that FFA may be associated with vitiligo . Whether this is merely a coincidence or a genuine association has not been conclusively elucidated.…”
Section: Discussionmentioning
confidence: 99%